URGENSI KETERSEDIAAN SARANA DAN PRASARANA DALAM MENDUKUNG MUTU PENDIDIKAN SEKOLAH DASAR - Rahayu Siregar, Suci; Firma Sari, Indah; Sukra Aulia, Fuji; Fadhilah, Rahma; Rafles Setiawan, Febliyen; Zikrinta Irzis Surbakti, M.; Reinita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the urgency of the availability of educational facilities and infrastructure in supporting the quality of education in elementary schools through a literature review approach of various scientific journals published within the last five years. The results indicate that educational facilities and infrastructure play a crucial role in enhancing the effectiveness and efficiency of the learning process. The availability of adequate facilities such as proper classrooms, learning media, libraries, and a conducive school environment can significantly improve students’ concentration, motivation, and learning outcomes. In addition, well-equipped facilities enable teachers to implement more varied, creative, and innovative teaching methods, making the learning process more interactive and meaningful. However, several challenges are still encountered, particularly in remote areas, including unequal distribution of facilities, limited financial resources, and suboptimal management. These conditions often result in underutilized and poorly maintained facilities. Therefore, integrated efforts among the government, schools, and communities are necessary to improve the availability and management of educational facilities and infrastructure. With adequate resources and effective management, the quality of education in elementary schools is expected to improve optimally and evenly across different regions.